THE INFLUENCE OF BUSINESS NETWORKS, BUSINESS CAPITAL, BUSINESS DURATION, AND TECHNOLOGY ON THE INCOME OF FASHION MSMEs IN WEST DENPASAR - Ni Komang Purnamianty; Ni Made Tisnawati (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This research is motivated by the importance of understanding the factors that influence the income of Micro, Small, and Medium Enterprises (MSMEs) in the fashion sector, particularly in West Denpasar District. The study aims to analyze the influence of business networks, business capital, business duration, and technology on the income of fashion MSMEs. It is expected to provide deeper insights into the dynamics of this sector and support the development of more effective policies. The research method used is a quantitative approach with an associative design. Data were collected through observation, structured interviews, and questionnaires distributed to 97 respondents selected using a stratified random sampling technique. Data analysis was conducted to examine the effect of the independent variables (business networks, business capital, business duration, and technology) on the dependent variable (fashion MSME income), both simultaneously and partially. The results show that business networks (X1), business capital (X2), business duration (X3), and technology (X4) simultaneously have a significant effect on the income of fashion MSMEs in West Denpasar District (Y). Partial testing also indicates that each of the variables—business networks (X1), business capital (X2), business duration (X3), and technology (X4)—has a significant influence on MSME income. This study highlights the importance of developing strong business networks to enhance market access and collaboration, as well as the need for investment in capital and technology to improve efficiency and competitiveness. Business duration also contributes positively to income, suggesting that MSME actors are encouraged to continuously develop their skills and knowledge.